Dirac and Klein-Gordon-Fock equations in Grumiller's spacetime - Al-Badawi, A.; Sakalli, I. (World Scientific Publ Co Pte Ltd, 2018)
We study the Dirac and the chargeless Klein-Gordon-Fock equations in the geometry of Grumiller's spacetime that describes a model for gravity of a central object at large distances. The Dirac equation is separated into radial and angular equations by adopting the Newman-Penrose formalism. The angular part of the both wave equations are analytically solved. For the radial equations, we managed to reduce them to one dimensional Schrodinger-type wave equations with their corresponding effective potentials. Fermions's potentials are numerically analyzed by serving their some characteristic plots. We also compute the quasinormal frequencies of the chargeless and massive scalar waves. With the aid of those quasinormal frequencies, Bekenstein's area conjecture is tested for the Grumiller black hole. Thus, the effects of the Rindler acceleration on the waves of fermions and scalars are thoroughly analyzed.
Keywords: Grumiller's spacetime; Dirac equation; Klein-Gordon-Fock equation; quantization; boson; fermion; adiabatic invariant